#72: Implementing an Algorithm-based Approach for Treatment of Fever and Neutropenia in Pediatric Oncology Patients in Tegucigalpa, Honduras. (26th March 2021) - Ordóñez, Sara; Luque, Marco; Zacasa, Pamela; Fu, Ligia; Peña, Armando; Caniza, Miguela; Mukkada, Sheena
Abstract: Background: Fever and neutropenia (FN) is a frequent complication in pediatric oncology patients, especially in high-risk patients. In our institution, 43% of acute lymphoblastic leukemia (ALL) patients in induction have at least one hospitalization for FN. A lack of institutional guidelines has led to misuse of antibiotics, prolonged antibiotic wait time and hospitalizations, and unnecessary venipunctures, among others. Implementing an algorithm has provided us with a baseline of previous FN management, and has led to an improvement in management as a whole and to critical areas such as lowering antibiotic wait time in these patients. Methods: Throughout 2017 we created and revised an algorithm for the management of FN based on current international FN guidelines and, tailored to our specific setting and needs. Orientation began 2 months prior to implementation, with intense training of residents, attendings, and nursing staff one month prior, and for the first 2 months of implementation. Active surveillance of adherence and outcomes, plus periodic retraining has been done throughout implementation. Adherence measurements include antibiotic wait time, use of antibiotics according to risk stratification, number of algorithm deviations, and collection of blood cultures. Results: Seventy-four patients met inclusion criteria from May 2018 to April 2019. Results were compared between early implementation, (first 3 months: group 1), to the remaining 9 months of the first year (group 2). Time to initial evaluation decreased by 75%, from 76.8 minutes in group 1 to 20.6 minutes in group 2 (P < 0.05). Antibiotic wait time decreased by 54.9%, from 5.18 hours to 2.3 hours (P = 0.0074). Time to blood culture was reduced by 65.3%, from 248 minutes to 85 minutes (P = 0.0040). Incorrect use of antibiotics according to risk stratification decreased by 59.2%, from 42% in group 1 to 17% in group 2 (P = 0.10). Total number of deviations decreased from 1.39 per patient to 1.17 per patient (P = 0.22; Table 1). Conclusions: Through initial and periodical training and active surveillance, key targets for adherence showed significant improvement throughout the first year of implementation. Maintaining communication with providers through monthly reports of audits, discussions of cases, and retraining improved awareness and willingness to adhere to protocol. Implementation has been particularly useful to residents and attendings outside of the Oncology Ward, where 49% of FN patients in our hospital are treated. It has provided standardized management, improved detection of cases, and reduced delays in care.